Pergeseran Nilai Sosial pada Hak Waris Perempuan Karo Muslim di Desa Budaya Lingga Kabupaten Karo - Lediyana Br Kaban; Suheri Harahap; Ahmed Fernanda Desky (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
This study examines the shift in social values in the inheritance rights of Karo Muslim women in Lingga Culture Village, Karo Regency. This research uses qualitative research and descriptive method. Information was collected through observation, in-depth interviews with traditional leaders, religious leaders, and Karo Muslim family members and documentation. The findings of the study reveal that there is a significant change in the distribution of inheritance rights of Karo Muslim women, from previously not getting their share to now being more fair and equal. The patriarchal culture in Karo society places men at a higher level than women. The Lingga Cultural Village community initially applied customary law, namely "Ajar dibata reh tua-tua sinuria" which means the teachings of ancestors in the distribution of inheritance rights, the inheritance of parents is only given to sons as heirs while daughters are not recognized as heirs and will only get "pemberen" which means gifts from parents. According to Max Waber's theory of social action, the division of inheritance rights is carried out using customary laws that have become social customs because these actions have meanings and values that are now showing a shift in Karo society. However, along with the times and increasing public awareness of the importance of gender equality, the rules for the distribution of inheritance in Lingga Cultural Village began to change. The occurrence of this social value shift is influenced by religious factors, education, jurisprudence, and globalization.